2011
DOI: 10.1111/j.1747-0285.2011.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of β‐Lactam Antibiotic‐Based Imidazolium‐ and Pyridinium‐Type Ionic Liquids

Abstract: We herein report the preparation and investigation of antibacterial activity of biocidal ionic liquids (ILs) consisting of cationic imidazolium or pyridinium and an anionic β-lactam antibiotic. The antibacterial properties were quantified by measuring the minimum inhibitory concentration and minimum bactericidal concentration against Escherichia coli O157:H7, Klebsiella pneumoniae, Staphylococcus aureus, and Enterococcus faecium. In general, the ILs had improved antibacterial activity than their parent materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 46 publications
0
71
0
Order By: Relevance
“…The combination of the [C 16 mim] cation with β -lactam antibiotics has been studied by Warner et al [12]. They reported that in more than 90 % of their cases the combination outperformed the commercially available antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the [C 16 mim] cation with β -lactam antibiotics has been studied by Warner et al [12]. They reported that in more than 90 % of their cases the combination outperformed the commercially available antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…A similar correlation between alkyl chain 1004 lengths/lipophilicity and antimicrobial activity was demonstrated 1005 for ILs using imidazolium and pyridinium derivatives as counteri- 1006 ons [136], or for ß-lactam antibiotics in which imidazolium-and 1007 pyridinium ILs displayed increased antimicrobial activity as com-1008 pared to the respective sodium salt [106]. 1009 In conclusion, the physical and chemical stability of ILs is an 1010 inherent concern to any amorphous or liquid formulation.…”
mentioning
confidence: 58%
“…Similarly, salt solvates, consisting of the API salt and neutral 104 (residual) solvent are between the two extremes of the pure salts 105 and pure co-crystal [5]. The liquid equivalents of salts are ILs, sto- 106 ichiometric combinations of completely ionized anions and 107 cations. The term IL is somewhat loosely defined such that crys- 108 talline and amorphous salts with a melting point below 100°C also 109 fulfill the definition of ILs.…”
mentioning
confidence: 99%
“…The combination of the adequate anion or cation with a specific drug can lead to an alteration in the The most conventional synthetic preparation of ILs involves a metathesis reaction of an anion halide with an adequate alkaline salt and this was also used in the preparation of some bulky imidazolium and pyridinium ILs containing an ampicillin anion. 26 The pure IL can be obtained by eliminating undesirable inorganic salts (mainly sodium, potassium or lithium chloride or bromide) using precipitation followed by filtration. 27 The need to obtain pure ILs, especially halide-free ones, has been one of the central concerns within the IL community.…”
Section: Introductionmentioning
confidence: 99%